Comparing significant factors affecting customer satisfaction in Bank Islam and RHB Bank / Ahmad Lufti Anis ... [et al.] - Anis, Ahmad Lufti; Awang Mohd Sulaiman, Awang Ikwan; Mohamad, Zamri
An increasingly competitive banking industry necessitates banks to know the changing needs and expectations of customers so as to devise and implement more effective marketing strategies. This study aims at identifying significant factors that influence customer satisfaction within the dimensions of service satisfaction, commitment, trust, communication and conflict handling. Bank Islam and RHB Bank were selected and samples were gathered through random sampling method. Consolidation with management of the respective banks showed that the findings correspond with current situation faced by the banks. Contributing factors to customer satisfaction both from the customers’ perspectives and bank managements’ perspectives within the scope of customer satisfaction are compared. Implications and future research are also discussed.